A Novel Method for Quantifying Contributions from Individual Muscles to Tremor: A Methodological Feasibility Study of Wrist Tremor - Nolan H. Howes; Dario Farina; Steven K. Charles (Annals of Biomedical Engineering, 2026)

Candidozyma auris Reported in Scotland: a Call for Vigilance Amid Global Rise - M. H. Howe; K. L. Bartie; W. G. Mackay; T. Inkster; S. Cairns; R. Kean; A. M. Bal; G. Ramage (Mycopathologia, 2026)
Candidozyma auris (formerly Candida auris ) is an emerging pathogenic yeast associated with healthcare outbreaks worldwide. Despite increasing reports across Europe, no published data have previously described cases in Scotland. Here, we report the first detections of C. auris in Scotland, as submitted to ARHAI Scotland. Eight cases (seven colonisations, one infection) were identified to date across four NHS Scotland boards, all linked to repatriation or recent hospitalisation abroad. To contextualise these findings, we reviewed publicly available literature and surveillance data for Western and Northern Europe, identifying considerable variation in case numbers and highlighting Scotland’s position among countries with the lowest reported cases. All Scottish cases were imported, underscoring the importance of targeted screening of patients with international healthcare exposure. These findings inform preparedness planning and support recommendations for strengthened surveillance to prevent onward transmission.

Soft Range Limits Shape Sensitivity to Forest Cover More Strongly Than Hard Range Limits - Natasha R. Granville; Alex L. Pigot; Benjamin Howes; Luiz dos Anjos; Victor Arroyo‐Rodriguez; Luc Barbaro; Jos Barlow; Matthew G. Betts; Alexis Cerezo; Pedro F. Develey; Jack H. Hatfield; Hervé Jactel; et al. (Global Ecology and Biogeography, 2025)
Aim Land‐use change is a major threat to biodiversity, yet there remains considerable unexplained variation in how it affects different populations of the same species. Here, we examine how sensitivity to forest cover changes depending on proximity to different limits of a species' range. By comparing responses as species approach their coastal (‘hard’) and inland (‘soft’) range limits, we aim to provide insight into the relative influence of mass effects, as compared to abiotic and biotic environmental suitability in shaping population sensitivity. Location Global. Time Period 1996–2019. Major Taxa Studied Birds. Methods We combined data from several large databases to obtain a dataset of 2543 bird species surveyed across 116 studies, spanning six continents. Using expert‐verified range maps, we calculated the position of populations relative to their species' nearest inland (‘soft’) and coastal (‘hard’) range limits and categorised the inland limits as equatorward‐ or poleward‐ facing. We investigated how distance to range limits and forest cover, derived from a 30 m‐resolution global dataset, affect the probability of species' incidence. Results We found that bird populations are more sensitive to forest cover when located closer to their species' inland (‘soft’) range limits, whereas this was not the case at coastal (‘hard’) range limits. The heightened sensitivity to forest cover at soft range limits was similar regardless of whether the range limit faced equatorward or poleward. Main Conclusions These results highlight how populations close to the soft limits of their species' ranges are at higher risk of extirpation resulting from loss of forest cover. This suggests that environmental conditions (e.g., climate), which become more challenging away from the core of the species' range, drive variability in sensitivity to forest cover.

Alignment between Duplex Sequencing and transgenic rodent mutation assay data in the assessment of in vivo NDMA-induced mutagenesis - Anne L. Ashford; Daniela Nachmanson; John W. Wills; Jacob E. Higgins; Thomas H. Smith; Kevin C. Vavra; Farah A. Dahalan; Jonathan Howe; Joanne M. Elloway; Jesse J. Salk; Ann Doherty; Anthony M. Lynch (Archives of Toxicology, 2025)

Cold Region River Flood Mapping and Scour Potential Prediction: Insights from Hydraulic Model Using Advanced Autonomous Surface Vehicles - Vida Atashi; Yeo Howe Lim; Taufiq H. Mahmood (Environmental Processes, 2024)
This study aimed to map the 2022 flood with a 16.5-year return period near a bridge on the Red River, close to Grafton City, North Dakota, and evaluate the scour potential around the bridge. The Red River Basin (RRB) near Grand Forks, ND, and Emerson, ND, is a cold region river vulnerable to floods. Local scouring around bridge piers during floods can lead to hydraulic structure failure. An Autonomous Surface Vehicle (ASV) equipped with LiDAR DEM data from the ND DWR’s LiDAR dataset was used to collect comprehensive bathymetry and discharge data, including the 2022 flood. The HEC-RAS model was used to create flood maps, and the Colorado State University (CSU) methodology was employed to assess local scour around the bridge pier. The study area recorded maximum velocities of 1.71 m/s, 1.87 m/s, and 1.56 m/s for discharge values of 368 m 3 /s, 784 m 3 /s, and 1335 m 3 /s, respectively, with higher velocities recorded upstream of the bridge. The maximum water depth reached 13.14 m during the peak discharge of 1335 m 3 /s. Higher discharge resulted in increased Froude number and contraction scour depth, with the latter continuing to increase even when the Froude number decreased as water reached the bridge deck. The study highlights the effectiveness of integrating ASVs, bathymetry, and LiDAR data to comprehensively understand flood dynamics and bridge scour in cold region rivers, offering the way for the development of effective flood control measures and strategies to safeguard critical infrastructure.

Quantification and classification of a giant fluvial-distributive system - the Triassic Mungaroo Formation, NWS, Australia - T.H.D. Payenberg; B.J. Willis; P. Sixsmith; S.D. Connell; A. Powell; K.T. Milliken; H.W. Posamentier; A. Allgoewer; E. Meyers; T. Marsh; M.D. Sullivan; S.C. Lang; et al. (Earth-Science Reviews, 2024)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

The benefits of regular aerobic exercise training on cerebrovascular function and cognition in older adults - Edward S. Bliss; Samia M. Biki; Rachel H. X. Wong; Peter R. C. Howe; Dean E. Mills (European Journal of Applied Physiology, 2023)
We compared the differences in cerebrovascular and cognitive function between 13 aerobic exercise trained, older adults and 13 age-, height- and sex-matched sedentary, untrained controls. We determined whether other measures accounted for differences in cerebrovascular and cognitive function between these groups and examined the associations between these functions. Participants undertook anthropometric, mood, cardiovascular, exercise performance, strength, cerebrovascular, and cognitive measurements, and a blood collection. Transcranial Doppler ultrasonography determined cerebrovascular responsiveness (CVR) to hypercapnia and cognitive stimuli. The trained group had a higher CVR to hypercapnia (80.3 ± 7.2 vs 35.1 ± 6.7%, P < 0.001), CVR to cognitive stimuli (30.1 ± 2.9 vs 17.8 ± 1.4%, P = 0.001) and total composite cognitive score (117 ± 2 vs 98 ± 4, P < 0.001) than the controls. These parameters no longer remained statistically different between the groups following adjustments for covariates. There were positive correlations between the total composite cognitive score and CVR to hypercapnia ( r = 0.474, P = 0.014) and CVR to cognitive stimuli ( r = 0.685, P < 0.001). We observed a relationship between cerebrovascular and cognitive function in older adults and an interaction between regular lifelong aerobic exercise training and cardiometabolic factors that may directly influence these functions.

Geographic and demographic variation in worry about extreme heat and COVID-19 risk in summer 2020 - Peter D. Howe; Olga V. Wilhelmi; Mary H. Hayden; Cassandra O'Lenick (Applied Geography, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Test–retest reliability of arterial spin labelling for cerebral blood flow in older adults with small vessel disease - Lauren R. Binnie; Mathilde M. H. Pauls; Philip Benjamin; Mohani-Preet K. Dhillon; Shai Betteridge; Brian Clarke; Rita Ghatala; Fearghal A. H. Hainsworth; Franklyn A. Howe; Usman Khan; Christina Kruuse; Jeremy B. Madigan; et al. (Translational Stroke Research, 2022)
Cerebral small vessel disease (SVD) is common in older people and is associated with lacunar stroke, white matter hyperintensities (WMH) and vascular cognitive impairment. Cerebral blood flow (CBF) is reduced in SVD, particularly within white matter. Here we quantified test–retest reliability in CBF measurements using pseudo-continuous arterial spin labelling (pCASL) in older adults with clinical and radiological evidence of SVD (N=54, mean (SD): 66.9 (8.7) years, 15 females/39 males). We generated whole-brain CBF maps on two visits at least 7 days apart (mean (SD): 20 (19), range 7-117 days). Test–retest reliability for CBF was high in all tissue types, with intra-class correlation coefficient [95%CI]: 0.758 [0.616, 0.852] for whole brain, 0.842 [0.743, 0.905] for total grey matter, 0.771 [0.636, 0.861] for deep grey matter (caudate-putamen and thalamus), 0.872 [0.790, 0.923] for normal-appearing white matter (NAWM) and 0.780 [0.650, 0.866] for WMH (all p<0.001). ANCOVA models indicated significant decline in CBF in total grey matter, deep grey matter and NAWM with increasing age and diastolic blood pressure (all p<0.001). CBF was lower in males relative to females (p=0.013 for total grey matter, p=0.004 for NAWM). We conclude that pCASL has high test–retest reliability as a quantitative measure of CBF in older adults with SVD. These findings support the use of pCASL in routine clinical imaging and as a clinical trial endpoint. All data come from the PASTIS trial, prospectively registered at: https://eudract.ema.europa.eu (2015-001235-20, registered 13/05/2015), http://www.clinicaltrials.gov (NCT02450253, registered 21/05/2015).

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study - Michael A. P. Bloomfield; Yumeya Yamamori; Chandni Hindocha; Augustus P. M. Jones; Jocelyn L. L. Yim; Hannah R. Walker; Ben Statton; Matthew B. Wall; Rachel H. Lees; Oliver D. Howes; Valerie H. Curran; Jonathan P. Roiser; et al. (Psychopharmacology, 2022)
Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models of its effects on anxiety. Methods We conducted a randomised, double-blind, placebo-controlled, crossover, acute oral challenge of 600 mg of CBD in 24 healthy participants on emotional processing, with neuroimaging (viewing emotional faces during functional magnetic resonance imaging) and cognitive (emotional appraisal) measures as well as subjective response to experimentally induced anxiety. Results CBD did not produce effects on brain responses to emotional faces and cognitive measures of emotional processing, or modulate experimentally induced anxiety, relative to placebo. Conclusions Given the rising popularity of CBD for its putative medical benefits, these findings question whether further research is warranted to investigate the clinical potential of CBD for the treatment of anxiety disorders.

Numbers matter: how irruptive bark beetles initiate transition to self-sustaining behavior during landscape-altering outbreaks - Michael Howe; Kenneth F. Raffa; Brian H. Aukema; Claudio Gratton; Allan L. Carroll (Oecologia, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Rodent suppression of seedling establishment in tropical pasture - Crystal A. Guzmán; Henry F. Howe; David H. Wise; Rosamond I. Coates; Jenny Zambrano (Oecologia, 2021)

Publisher Correction to: Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Leveraging a Landscape-Level Monitoring and Assessment Program for Developing Resilient Shorelines throughout the Laurentian Great Lakes - Donald G. Uzarski; Douglas A. Wilcox; Valerie J. Brady; Matthew J. Cooper; Dennis A. Albert; Jan J. H. Ciborowski; Nicholas P. Danz; Anne Garwood; Joseph P. Gathman; Thomas M. Gehring; Greg P. Grabas; Robert W. Howe; et al. (Wetlands, 2019)

Transforming growth factor-β promotes basement membrane fibrosis, alters perivascular cerebrospinal fluid distribution, and worsens neurological recovery in the aged brain after stroke - Matthew D. Howe; J. Weldon Furr; Yashasvee Munshi; Meaghan A. Roy-O’Reilly; Michael E. Maniskas; Edward C. Koellhoffer; John d’Aigle; Lauren H. Sansing; Louise D. McCullough; Akihiko Urayama (GeroScience, 2019)

Tobacco smoking and dopaminergic function in humans: a meta-analysis of molecular imaging studies - Abhishekh H. Ashok; Yuya Mizuno; Oliver D. Howes (Psychopharmacology, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Excitation transfer and trapping kinetics in plant photosystem I probed by two-dimensional electronic spectroscopy - Parveen Akhtar; Cheng Zhang; Zhengtang Liu; Howe-Siang Tan; Petar H. Lambrev (Photosynthesis Research, 2018)

Scientific Considerations for the Assessment and Management of Mine Tailings Disposal in the Deep Sea - Lindsay L. Vare; Maria C. Baker; John A. Howe; Lisa A. Levin; Carlos Neira; Eva Z. Ramirez-Llodra; Amanda Reichelt-Brushett; Ashley A. Rowden; Tracy M. Shimmield; Stuart L. Simpson; Eulogio H. Soto (Frontiers in Marine Science, 2018)

Generation of transgenic goats by pronuclear microinjection: a retrospective analysis of a commercial operation (1995–2012) - W. Gavin; S. Blash; N. Buzzell; D. Pollock; L. Chen; N. Hawkins; J. Howe; K. Miner; J. Pollock; C. Porter; M. Schofield; Y. Echelard; et al. (Transgenic Research, 2018)

Using Stable Isotopes to Assess the Contribution of Terrestrial and Riverine Organic Matter to Diets of Nearshore Marine Consumers in a Glacially Influenced Estuary - Emily J. Whitney; Anne H. Beaudreau; Emily R. Howe (Estuaries and Coasts, 2018)

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

Summer temperature variability across four urban neighborhoods in Knoxville, Tennessee, USA - Kelsey N. Ellis; Jon M. Hathaway; Lisa Reyes Mason; David A. Howe; Thomas H. Epps; Vincent M. Brown (Theoretical and Applied Climatology, 2017)

Influences of Natural and Anthropogenic Factors and Tidal Restoration on Terrestrial Arthropod Assemblages in West Coast North American Estuarine Wetlands - Aaron T. David; Pascale A. L. Goertler; Stuart H. Munsch; Brittany R. Jones; Charles A. Simenstad; Jason D. Toft; Jeffery R. Cordell; Emily R. Howe; Ayesha Gray; Michael P. Hannam; William Matsubu; Erin E. Morgan (Estuaries and Coasts, 2016)

Editorial: Reporting guidelines for psychopharmacology - Thomas Steckler; H. Valerie Curran; Harriet de Wit; Oliver Howes; Daniel Hoyer; Irwin Lucki; Klaus A. Miczek; A. Leslie Morrow; Lawrence H. Price; Trevor W. Robbins (Psychopharmacology, 2016)

Analytic laboratory performance of a point of care urine culture kit for diagnosis and antibiotic susceptibility testing - E. Bongard; N. Frimodt-Møller; M. Gal; M. Wootton; R. Howe; N. Francis; H. Goossens; C. C. Butler (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

The link between dopamine function and apathy in cannabis users: an [18F]-DOPA PET imaging study - Michael A. P. Bloomfield; Celia J. A. Morgan; Shitij Kapur; H. Valerie Curran; Oliver D. Howes (Psychopharmacology, 2014)

Associative blocking to reward-predicting cues is attenuated in ketamine users but can be modulated by images associated with drug use - Tom P. Freeman; Celia J. A. Morgan; Fiona Pepper; Oliver D. Howes; James M. Stone; H. Valerie Curran (Psychopharmacology, 2013)

Molecular mapping of adult plant stripe rust resistance in wheat and identification of pyramided QTL genotypes - H. S. Bariana; U. K. Bansal; A. Schmidt; A. Lehmensiek; J. Kaur; H. Miah; N. Howes; C. L. McIntyre (Euphytica, 2010)

Directional gene flow patterns in disjunct populations of the black ratsnake (Pantheropis obsoletus) and the Blanding’s turtle (Emydoidea blandingii) - Briar J. Howes; Joseph W. Brown; H. Lisle Gibbs; Tom B. Herman; Stephen W. Mockford; Kent A. Prior; Patrick J. Weatherhead (Conservation Genetics, 2009)

Integrated Measures of Anthropogenic Stress in the U.S. Great Lakes Basin - Nicholas P. Danz; Gerald J. Niemi; Ronald R. Regal; Tom Hollenhorst; Lucinda B. Johnson; JoAnn M. Hanowski; Richard P. Axler; Jan J. H. Ciborowski; Thomas Hrabik; Valerie J. Brady; John R. Kelly; John A. Morrice; et al. (Environmental Management, 2007)

Litter hovels as havens for riparian spiders in an unregulated river - Matthew R. Loeser; Bradner H. McRae; Marisa M. Howe; Thomas G. Whitham (Wetlands, 2006)

A national framework for cancer surveillance in the United States - Phyllis A. Wingo; Holly L. Howe; Michael J. Thun; Rachel Ballard-Barbash; Elizabeth Ward; Martin L. Brown; JoAnne Sylvester; Gilbert H. Friedell; Linda Alley; Julia H. Rowland; Brenda K. Edwards (Cancer Causes & Control, 2005)

Highly variable SSR markers in Douglas-fir: Mendelian inheritance and map locations - G. T. Slavov; G. T. Howe; I. Yakovlev; K. J. Edwards; K. V. Krutovskii; G. A. Tuskan; J. E. Carlson; S. H. Strauss; W. T. Adams (Theoretical and Applied Genetics, 2004)

Expression of a Truncated Brca1 Protein Delays Lactational Mammary Development in Transgenic Mice - Melissa A. Brown; Hans Nicolai; Kathy Howe; Toyomasa Katagiri; El-Nasir Lalani; Kaylene J. Simpson; Nathan W. Manning; Andrew Deans; Phil Chen; Kum Kum Khanna; Mas Rina Wati; Beatrice L. Griffiths; et al. (Transgenic Research, 2002)

A rodent plague on prairie diversity - H. F. Howe; J. S. Brown; B. Zorn‐Arnold (Ecology Letters, 2002)
Selective vole ( Microtus pennsylvanicus ) suppression of prairie grasses and forbs in experimental restorations suggests why many of the plants are likely to be uncommon in nature. Vole herbivory reduced densities of legumes and grasses and increased unpalatable forbs in replicated plantings in Illinois: six otherwise common species ( Dalea purpurea , Desmanthus illinoensis , Elymus canadensis , Panicum virgatum , Phalaris arundinacea , Sorghastrum nutans ) declined 27–89% in abundance, whereas two species ( Echinacea purpurea and Rudbeckia hirta ) increased by 61% and 1023%. Species number dropped by 19% and plant diversity (Simpson’s D) by 37% in one treatment to which voles had access. Plots were planted with 18 prairie species of the region, but in even distributions of 35 or 350 seeds species −1 m −2 , rather than skewed in favour of large C 4 grasses common in native remnants. Manipulation of plant composition and vole access revealed what are likely to be formative effects of rodent herbivory on vegetative composition. These experimental tallgrass communities appear to be assembling from plant species that voles prefer not to eat.

Low Recruitment of Trees Dispersed by Animals in African Forest Fragments - N. J. Cordeiro; H. F. Howe (Conservation Biology, 2001)
We investigated the effects of forest fragmentation on the disappearance of fruit‐eating animals and the recruitment of animal‐, wind‐, and gravity‐dispersed trees in 80‐year‐old forest patches in the East Usambara Mountains of Tanzania. We compared adult and juvenile trees in forest transects in a 3500–ha submontane forest with those in four forest fragments of 521, 30, 9, and 0.5 ha. Preliminary results show that recruitment of seedlings and juveniles of 31 animal‐dispersed tree species was more than three times greater in continuous forest and large forest fragments (≥30 ha) than in small forest fragments (≤9 ha), whereas recruitment of eight wind‐ and gravity‐dispersed trees of the forest interior was unaffected. Recruitment of 10 endemic, animal‐dispersed tree species was 40 times lower in small fragments than in continuous forest or large fragments. Counts of diurnal primates and birds in all five sites indicated that frugivorous species have declined with decreasing fragment size. These results are consistent with the idea that loss of dispersal agents depresses tree recruitment in the course of forest fragmentation.

DNA extraction from plants: The use of pectinase - Steven H. Rogstad; Brian Keane; Carolyn Howes Keiffer; Fred Hebard; Paul Sisco (Plant Molecular Biology Reporter, 2001)

Organisation and expression of the plastid genome of the dinoflagellate Amphidinium operculatum - A. Barbrook; H. Symington; R. Nisbet; A. Larkum; C. Howe (Molecular Genetics and Genomics, 2001)

Quantitative genetics of bud phenology, frost damage, and winter survival in an F2 family of hybrid poplars - G. T. Howe; P. Saruul; J. Davis; T. H. H. Chen (Theoretical and Applied Genetics, 2000)

Leftward shift in the acquisition of cocaine self-administration in isolation-reared rats: relationship to extracellular levels of dopamine, serotonin and glutamate in the nucleus accumbens and amygdala-striatal FOS expression - Simon R. Howes; Jeffrey W. Dalley; Caroline H. Morrison; Trevor W. Robbins; Barry J. Everitt (Psychopharmacology, 2000)

Comparative Use of Riparian Corridors and Oases by Migrating Birds in Southeast Arizona - Susan K. Skagen; Cynthia P. Melcher; William H. Howe; Fritz L. Knopf (Conservation Biology, 1998)

Comparative Use of Riparian Corridors and Oases by Migrating Birds in Southeast Arizona - Susan K. Skagen; Cynthia P. Melcher; William H. Howe; Fritz L. Knopf (Conservation Biology, 1998)
The relative importance of cottonwood‐willow riparian corridors and isolated oases to land birds migrating across southeastern Arizona was evaluated during four spring migrations, 1989 to 1994, based on patterns of species richness, relative abundance, density, and body condition of birds. We surveyed birds in 13 study sites ranging in size and connectivity from small isolated patches to extensive riparian forest, sampled vegetation and insects, and captured birds in mistnets. The continuous band of riparian vegetation along the San Pedro River does not appear to be functioning as a corridor for many migrating species, although it may for a few, namely Yellow‐breasted Chats ( Icteria virens ), Summer Tanagers ( Piranga rubra ), and Northern Rough‐winged Swallows ( Steldigopteryx serripennis ), which account for fewer than 10% of the individuals migrating through the area. Small, isolated oases hosted more avian species than the corridor sites, and the relative abundances of most migrating birds did not differ between sites relative to size‐connectivity. There were few differences in between‐year variability in the relative abundances of migrating birds between corridor and oasis sites. Between‐year variability decreased with overall abundance of species and was greater for species with breeding ranges that centered north of 50°N latitude. Body condition of birds did not differ relative to the size‐connectivity of the capture site, but individuals of species with more northerly breeding ranges had more body fat than species that breed nearby. Peak migration densities of several bird species far exceeded breeding densities reported for the San Pedro River, suggesting that large components of these species were en route migrants. Peak densities of Yellow Warblers ( Dendroica petechia ) reached 48.0 birds/ha, of Wilson’s Warblers ( Wilsonia pusilla ) 33.7 birds/ha, and of Yellow‐rumped Warblers ( D. coronata ) 30.1 birds/ha. Riparian vegetation is limited in extent in the vicinity of our study sites, covering less than 1% of the landscape. We conclude that all riparian patches in southeastern Arizona are important as stopover sites to en route migrants regardless of their size and degree of isolation or connectivity. In light of potential habitat limitation, the protection of both small, disjunct riparian patches and extensive riverine tracts in western landscapes is imperative. Uso Comparativo de Corredores Riparios y Oasis por Aves Migratorias en el Sureste de Arizona Se evaluó la importancia relativa de los corredores riparios de sauces y los oasis aislados para las aves que migran a través del sureste de Arizona durante cuatro migraciones de primavera, de 1989 a 1994, en base a patrones de riqueza de especies, abundancia relativa, densidades y condición corporal de las aves. Estudiamos aves en 13 sitios variando en tamaño y conectividad desde parches pequeños aislados hasta bosques riparios extensos. Muestreamos la vegetación e insectos y capturamos aves con redes. Las bandas continuas de vegetación riparia a lo largo del rio San Pedro no aparenta funcionar como un corredor para muchas de las aves migratorias, aunque podría serlo para algunas tales como: Icteria virens , Piranga rubra y Steldigopteryx serripennis , las cuales corresponen a menos de un 10% de los individuos migrando a través del área. Los oasis pequeños aislados hospedaron mas especies de aves que los sitios de corredor y las abundancias relativas de la mayoría de las especies migrando no fue diferente entre sitios en relación con el tamaño de la conectividad. Existieron pocas diferencias en variabilidad de la abundancia relativa entre años entre los corredores y los sitios con oasis. La variabilidad entre años disminuyó en general con la abundancia de especies y fue mayor para especies con rangos reproductivos centrados al norte de los 50° latitud norte. La condición corporal de las aves no difirió en relación con el tamaño de la conectividad del sitio de captura, pero los individuos de especies con rangos de reproducción mas hacia el norte tuvieron mas grasa corporal que las especies que se reproducen en las cercanías. Las densidades pico de migración de varias de las especies de aves excedio por mucho las densidades reproductivas reportadas para el rio San Pedro, sugiriendo que los componentes grandes de estas especies fueron migrantes en ruta. Las densidades pico de Dendroica petechia alcanzó los 48.0 aves/ha, Wilsonia pusilla 33.7 aves/ha y D. coronata 30.1 aves/ha. La vegetación riparia esta limitada en extensión en las áreas vecinas al sitio de estudio, cubriendo menos de 1% del paisaje. Concluimos que todos los parches riparios en el sureste de Arizona son importantes como sitios de reposo para migrantes en ruta independientemente del tamaño y el grado de aislamiento o conectividad. En vista de la potencial limitante del habitat, es imperante la protección tanto de parches pequeños disjuntos como de áreas riverinas extensas en los paisajes del oeste.

Annual cycles of phytoplankton community-structure and bloom dynamics in the Neuse River Estuary, North Carolina - J. L. Pinckney; H. W. Paerl; M. B. Harrington; K. E. Howe (Marine Biology, 1998)

Design of a summary screen for an ICU patient data management system - R. H. Ireland; H. V. James; M. Howes; A. J. Wilson (Medical & Biological Engineering & Computing, 1997)

The relationship between dietary fat intake and risk of colorectal cancer: evidence from the combined analysis of 13 case-control studies - Geoffrey R. Howe; Kristan J. Aronson; Enrique Benito; Roberto Castelleto; Jacqueline Cornée; Stephen Duffy; Richard P. Gallagher; José M. Iscovich; Jiao Deng-ao; Rudolf Kaaks; Gabriel A. Kune; Susan Kune; et al. (Cancer Causes & Control, 1997)

Non-dietary factors as risk factors for breast cancer, and as effect modifiers of the association of fat intake and risk of breast cancer - David J. Hunter; Donna Spiegelman; Hans-Olov Adami; Piet A. van den Brandt; Aaron R. Folsom; R. Alexandra Goldbohm; Saxon Graham; Goeffrey R. Howe; Lawrence H. Kushi; James R. Marshall; Anthony B. Miller; Frank E. Speizer; et al. (Cancer Causes & Control, 1997)

Biological components of Sites of Special Scientific Interest in Wales - T. H. Blackstock; D. P. Stevens; E. A. Howe (Biodiversity and Conservation, 1996)

Effect of carbon source on enzymes involved in glycerol metabolism inNeurospora crassa - Gary D. Tom; M. Viswanath-Reddy; H. Branch Howe (Archives of Microbiology, 1978)

Temperature-dependent actinomycin D effect on RNA synthesis during synchronous development in Neurospora crassa - R. E. Totten; H. Branch Howe (Biochemical Genetics, 1971)